2018
DOI: 10.1097/aud.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Utricular Response Using oVEMP and Unilateral Centrifugation Rotation Testing

Abstract: Various anatomical and physiological differences within the utricle, in addition to the fundamental differences in stimulus properties between the oVEMP and UCF tests, could explain the lack of significant correlations between these measures and suggest that oVEMP and UCF testing may be complimentary in their evaluation of the utricular system. These data reinforce the complexities of the utricular system and provide further insight into the difficulties encountered in its clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The sustained and transient modes of otolithic operation have an interesting consequencethat there could be a dissociation between the results of the low frequency and high frequency tests. That has been confirmed in healthy subjects by [93] who found no correlation between ocular torsion (bias) (low frequency) and oVEMPs (high frequency), indicating the two types of tests are probing different functions. In the case of patients, complete unilateral loss of otolith function abolishes both high and low frequency responses, but in other patients, one or the other of the high frequency or low frequency response modes could be affected whilst leaving the other mode intact.…”
Section: Tests Of the Transient System Of Otolith Functionmentioning
confidence: 84%
“…The sustained and transient modes of otolithic operation have an interesting consequencethat there could be a dissociation between the results of the low frequency and high frequency tests. That has been confirmed in healthy subjects by [93] who found no correlation between ocular torsion (bias) (low frequency) and oVEMPs (high frequency), indicating the two types of tests are probing different functions. In the case of patients, complete unilateral loss of otolith function abolishes both high and low frequency responses, but in other patients, one or the other of the high frequency or low frequency response modes could be affected whilst leaving the other mode intact.…”
Section: Tests Of the Transient System Of Otolith Functionmentioning
confidence: 84%
“…A recent report did not detect a relationship between SVV and oVEMPs in healthy subjects. 32 This is not unexpected given that the subjects were healthy individuals, so the variability needed to establish such a relationship would have been very small. When patients are tested the relationship is clear.…”
Section: Clinical Profiles Asymmetry Ratiomentioning
confidence: 94%
“…In addition, the OCR is primarily associated with utricular function. It is an important future research direction to assess vestibular functions that associate with MS susceptibility using VEMP because VEMP and OCR are complemental for vestibular assessment (36). In addition, as several studies suggested, the role of individual differences in other cortical functions, such as multisensory integration and psychological processes, in the development of MS should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, a widely used clinical test is the vestibular evoked myogenic potentials (VEMP) test in which each unilateral otolith can be separately stimulated by bone/air conduction of sound (34,35). The VEMP and OCR are complementary tests that evaluate different aspects of otolith function (36). For the aim of this study, we adopted the OCR and HT-SVV tests providing different outcomes to compared the impacts of asymmetry in reflex and cortical pathways on MS susceptibility using the same vestibular stimulation (i.e., lateral head tilt) with the HT-SVV test.…”
Section: Introductionmentioning
confidence: 99%